ESE Formula Sheet
ESE Formula Sheet
ESE Formula Sheet
0,
Basics (Set theory, Axioms of Probability, Total Probability, Baye’s Theorem)
… ,
|"
#$%
, &
#%
'
|
'
|
|(
(
( |
|
'
|
)
* ! !
-0 ,, 1 ,
, . &
-
- , . &
,! ,! ,!
23
4 5 23 ∞ 1, 23 ∞ 0, 23 , &
8
9 4 5 * 23 * 23 &23
Distribution and Density Functions (Single Random Variable)
:3 ;
&
1 PQR, :3 S
>TB , U 0
= B
:3 ?
( @ (
B>MN
< :3 1 23 < :3 A&A CDEFFGDH, :3
>
ON
>= >= √2KL *
1 1 >B N >B N K 4K *
PQR, 23 1
>TB , U 0, V
, * WDXYPGCZ, :3 *
*ON , 23 1
*ON , U 0, V
L[ , L
S S L 2 2
1 ^GH_`GDY, :3 - - 1>- , V
, 1
EHG], :3 , 5 5 ^, 23 , 5 5 ^, 1, U ^
^ ^
S -
CP_`PaWGb H_ _] cPWH_EYYG aWGDYF EHaGY ]GWFa FEbbPFF,
, :3
R_GFF_H,
, :3
>T , V
S 1 1
,! 1 -> , V
, ,
*
:B | =
2B 2B g :B g
|4
<
|4 :3 & 23 d4 5 e4 f gh , Ri]
:B >= 1 2B g 1 2B g
= =
no4 ^mp no4p ^nomp
Expectations
1
bPHaWDY YG`Ga, ¾ 4 ' 4 , x V
r, L * 9 ∞ j ¾ Ã ¾~Êr, L *
Stochastic Processes
¤· ¢da h…a BÆ ,…,B· ;¼Æ ,…,¼·
HaZ _WiPW , 2aÆ …aH Æ , … , ; Æ , … ,
®4 5 , … , 4 5 , :aÆ …aH Æ , … , ; Æ , … , Æ H
¤Bª …¤B·
2 ; 2 , ∞; , * = =
no4 * p Ì,
: ; < : , * ; , * &* r3 n4p < :; &
>= >=
= =
DEa_b_tDW, , * Ì , * r3 r3 *
DEa_b_WW, Ìxx, * no44*p < < *:, *; , *&*
>= >=
, * bW_FF b_WW, Ì3k , * no4 m* p bW_FF b_tDW, , *
b_WW b_P]], , *
Í, *, * Ì3k , *
r3 rk *
¿ZGaP H_GFP, , * 0, * , r 0, Î 1@Î ±±±, :aÆ …aH Æ , … , ; Æ , … , :aÆ …aH Æ , … , ; Æ b, … ,
Î
±±, V
, no4 4* p Ì * ÌÎ, no4 * p Ì0, Î ÌÎ |r|* , Î , ÌÎ ÌÎ, Ì0 U ÌÎ
0
Ï_GHaYX ±±, no4 4* p Ì3k * Ì3k Î, 3k Î Ì3k Î r3 rk
m , 4 `P`_WXYPFF, m &
& 4 ) V
V.
j
Systems with Stochastic Inputs
=
YGHPDW, m Ðo4p 4 Ñ < 4 gg&g, x
Ðo@p, n¬Ðo4p Ьno4p, 4 m
>=
=
YGHPDW, 4Ò
mÒ, Ó, 48 m8 , YGHPDW, nomp no4p Ñ r3 < g&g
>=
= =
1 =
YGHPDW, Ì3k , * < Ì33 , * gg&g , Ìkk ? R_¿PW FRPb, Õ ÖÌÎ < ÌÎ
>y×Ø
&Î j ÌÎ < Õ
y×¼ &Õ
>= >= 2K >=
ÙÚ Û ±Ü, @Î Û 1,1 Û 2K@Õ,
yÝØ Û 2K@Õ Þ
1 B 1 1 >B« «
Integration (all integrals are w.r.t x)
<
ß B
< || <
ß B«
< < sin cos < cos
ß ß 1
1 ß B« 1 1
< tan ln || <
ß B« ß
< > « < l < A
ß 1
& & l A &. &. & & & ß B &
Differentiation
l A æ ç >
ß
ß B
æ
Bç
B
& & * & & & & & & *
& &
sin cos cos
& &
^ 1 *
è è & ^
Matrix Operations
& >
é ê ,
: ë
|| * ** (y
Prepared by: Hammad Munawar (Institute of Avionics and Aeronautics, Islamabad, Pakistan) hammadmunawar@gmail.com
(COPYRIGHT STATEMENT: May be used / distributed / edited freely, as long as the name of the original author is included)
Table of Integrals∗
Basic Forms Integrals with Logarithms
√ √
Z
2
Z x ax + bdx = (−2b2 + abx + 3a2 x2 ) ax + b (26)
1
Z
x dx = n
xn+1 (1) 15a2
ln axdx = x ln ax − x (42)
n+1
Z
1
Z
ln ax 1
dx = ln |x| (2) Z p
1 dx = (ln ax)2 (43)
x
h
x(ax + b)dx =
p
(2ax + b) ax(ax + b) x 2
Z Z 4a3/2
√
udv = uv − vdu (3) p i
−b2 ln a x + a(ax + b)
Z
(27) b
ln(ax + b)dx = x + ln(ax + b) − x, a 6= 0 (44)
Z a
1 1
dx = ln |ax + b| (4)
ax + b a Z
x
b2 ln(x2 + a2 ) dx = x ln(x2 + a2 ) + 2a tan−1
Z p
Integrals of Rational Functions b x p 3 − 2x (45)
x3 (ax + b)dx = − 2 + x (ax + b) a
12a 8a x 3
b3
√ p
+ 5/2 ln a x + a(ax + b) (28)
Z
1 1
Z
8a x+a
dx = − (5) ln(x2 − a2 ) dx = x ln(x2 − a2 ) + a ln − 2x (46)
(x + a)2 x+a x−a
(x + a)n+1
Z
(x + a)n dx = , n 6= −1 (6) Z
1p 2ax + b
Z p
n+1 1 p 1
ln ax2 + bx + c dx = 4ac − b2 tan−1 √
p
= x x2 ± a2 ± a2 ln x + x2 ± a2
x2 ± a2 dx
2 2 a 4ac − b2
Z
(x + a)n+1 ((n + 1)x − a) (29)
b
x(x + a)n dx = + x ln ax2 + bx + c
(7) − 2x + (47)
(n + 1)(n + 2) 2a
Z
1 Z p
1 p 2 1 x
dx = tan−1 x (8) a2 − x2 dx = x a − x2 + a2 tan−1 √
Z
bx 1
1 + x2 2 2 a2 − x2 x ln(ax + b)dx = − x2
2a 4
Z
1 1 x (30)
dx = tan−1 b2
(9) 1
a2 + x2 a a + x2 − 2 ln(ax + b) (48)
Z 2 a
Z
x 1
p 1 2 3/2
dx = ln |a2 + x2 | (10) x x2 ± a2 dx = x ± a2 (31)
a2 + x2 2 3 Z
1
x ln a2 − b2 x2 dx = − x2 +
Z 2
x x Z 2
dx = x − a tan−1 1
(11)
p
√ dx = ln x + x2 ± a2 (32)
a2 + x2 a x2 ± a2 1
a2
x − 2 ln a2 − b2 x2
2
(49)
Z
x3 1 1 2 b
dx = x2 − a2 ln |a2 + x2 | (12) Z
1 x
a + x2
2 2 2 √ dx = sin−1 (33)
a2 − x2 a Integrals with Exponentials
Z
1 2 2ax + b
dx = √ tan−1 √ (13) Z
x
ax2 + bx + c 4ac − b 2 4ac − b2
p Z
√ dx = x2 ± a2 (34) 1 ax
x ±a
2 2 eax dx = e (50)
a
Z
1 1 a+x
, a 6= b √
Z
dx = ln (14) x p
√ 1 √ ax √
Z
(x + a)(x + b) b−a b+x √ dx = − a2 − x2 (35) i π
a −x
2 2 xeax dx = xe + 3/2 erf i ax ,
Z a 2a
x a 2
Z x
dx = + ln |a + x| (15) where erf(x) = √
2
e−t dt (51)
(x + a)2 a+x π 0
x2
Z
1 p 1
p
√ dx = x x2 ± a2 ∓ a2 ln x + x2 ± a2
Z
x 1 x ±a
2 2 2 2 Z
dx = ln |ax2 + bx + c| (36) xex dx = (x − 1)ex (52)
ax2 + bx + c 2a
b 2ax + b
tan−1 √
− √
Z
(16) x 1
a 4ac − b2 4ac − b2 xeax dx = − 2 eax (53)
Z p
b + 2ax p 2 a a
Integrals with Roots ax2 + bx + cdx = ax + bx + c
4a
Z
x2 ex dx = x2 − 2x + 2 ex
2
(54)
4ac − b
p
+ ln
+ b + 2 a(ax2 + bx+ c) (37)
√
Z
2 8a3/2
2ax
x − adx = (x − a)3/2 (17) x2
Z
2x 2
3 x2 eax dx = − 2 + 3 eax (55)
a a a
√
Z
1
√ dx = 2 x ± a (18)
Z
1 √ p 2 x3 ex dx = x3 − 3x2 + 6x − 6 ex
Z
x±a p (56)
x ax2 + bx + c = 2 a ax + bx + c
Z
1 √ 48a5/2
√ dx = −2 a − x (19) xn eax
Z Z
× −3b2 + 2abx + 8a(c + ax2 ) n
a−x xn eax dx = − xn−1 eax dx (57)
√ p a a
+3(b3 − 4abc) ln b + 2ax + 2 a ax2 + bx + c (38)
√
Z
2 2
x x − adx = a(x − a)3/2 + (x − a)5/2 (20) Z
(−1)n
3 5 xn eax dx = Γ[1 + n, −ax],
an+1
Z
√
√ Z ∞ (58)
2b 2x Z
1 1 ta−1 e−t dt
ax + bdx = + ax + b (21) where Γ(a, x) =
p
√ dx = √ ln 2ax + b + 2 a(ax2 + bx + c)
3a 3 ax2 + bx + c a x
Z
2 (39) √
√
Z
(ax + b)3/2 dx = (ax + b)5/2 (22) 2 i π
eax dx = − √ erf ix a (59)
5a 2 a
√ √
Z
x 2 Z
√
√ dx = (x ∓ 2a) x ± a (23) π
Z 2
x 1p 2 e−ax dx = √ erf x a (60)
x±a 3 √ dx = ax + bx + c
ax2 + bx + c a 2 a
b
Z
p p 2 1 2
x(a − x) − 3/2 ln 2ax + b + 2 a(ax2 + bx + c) xe−ax dx = − e−ax
Z r
(40)
x (61)
dx = − x(a − x) − a tan−1
p
(24) 2a 2a
a−x x−a
√
Z Z r
dx x 2 −ax2 1 π x −ax2
√ = √ (41) x e dx = erf(x a) − e (62)
Z r
x p √
(a2 + x2 )3/2 4 a3 2a
dx = x(a + x) − a ln x + x + a (25) a2 a2 + x2
a+x
∗
« 2014. From http://integral-table.com, last revised June 14, 2014. This material is provided as is without warranty or representation about the accuracy, correctness or
suitability of the material for any purpose, and is licensed under the Creative Commons Attribution-Noncommercial-ShareAlike 3.0 United States License. To view a copy of this
license, visit http://creativecommons.org/licenses/by-nc-sa/3.0/ or send a letter to Creative Commons, 171 Second Street, Suite 300, San Francisco, California, 94105, USA.
www.mathportal.org
1
Table of Distributions
Bernoulli P (X = 1) = p
Bern(p) P (X = 0) = q = 1 − p p pq q + pet
n k n−k
Binomial P (X = k) = k
p q
Bin(n, p) k ∈ {0, 1, 2, . . . n} np npq (q + pet )n
Geometric P (X = k) = q k p
p
Geom(p) k ∈ {0, 1, 2, . . . } q/p q/p2 1−qet
, qet < 1
r+n−1 r n
Negative Binomial P (X = n) = r−1
p q
p
NBin(r, p) n ∈ {0, 1, 2, . . . } rq/p rq/p2 ( 1−qe r t
t ) , qe < 1
w+b
P (X = k) = w b /
Hypergeometric k n−k n
nw w+b−n µ µ
HGeom(w, b, n) k ∈ {0, 1, 2, . . . , n} µ= b+w w+b−1
nn (1 − n
) messy
e−λ λk
Poisson P (X = k) = k!
t
Pois(λ) k ∈ {0, 1, 2, . . . } λ λ eλ(e −1)
1
Uniform f (x) = b−a
a+b (b−a)2 etb −eta
Unif(a, b) x ∈ (a, b) 2 12 t(b−a)
2 2
f (x) = √1 e−(x − µ) /(2σ )
Normal σ 2π
σ 2 t2
N (µ, σ 2 ) x ∈ (−∞, ∞) µ σ2 etµ+ 2
1
f (x) = Γ(a)
(λx)a e−λx x1
Gamma a
a a λ
Gamma(a, λ) x ∈ (0, ∞) λ λ2 λ−t
,t<λ
Γ(a+b) a−1
f (x) = Γ(a)Γ(b)
x (1 − x)b−1
Beta
a µ(1−µ)
Beta(a, b) x ∈ (0, 1) µ= a+b (a+b+1)
messy
2
1
√ e−(log x−µ) /(2σ 2 )
Log-Normal xσ 2π
2 2
LN (µ, σ 2 ) x ∈ (0, ∞) θ = eµ+σ /2 θ2 (eσ − 1) doesn’t exist
1
Chi-Square xn/2−1 e−x/2
2n/2 Γ(n/2)
χ2n x ∈ (0, ∞) n 2n (1 − 2t)−n/2 , t < 1/2
Γ((n+1)/2)
√
nπΓ(n/2)
(1 + x2 /n)−(n+1)/2
Student-t
n
tn x ∈ (−∞, ∞) 0 if n > 1 n−2
if n > 2 doesn’t exist
Table of Laplace Transforms
f ( t ) = L -1 {F ( s )} F ( s ) = L { f ( t )} f ( t ) = L -1 {F ( s )} F ( s ) = L { f ( t )}
1 1
1. 1 2. e at
s s-a
n! G ( p + 1)
3. t n , n = 1, 2,3,K 4. t p , p > -1
s n +1 s p +1
p 1 × 3 × 5L ( 2n - 1) p
, n = 1, 2,3,K
n - 12
5. t 3 6. t n+ 1
2s 2
2n s 2
a s
7. sin ( at ) 8. cos ( at )
s + a2
2
s + a2
2
2as s2 - a2
9. t sin ( at ) 10. t cos ( at )
(s + a2 ) (s + a2 )
2 2 2
2
2a 3 2as 2
11. sin ( at ) - at cos ( at ) 12. sin ( at ) + at cos ( at )
(s + a )
2 2 2
(s + a )
2 2 2
s(s - a ) 2 2
s ( s + 3a )
2 2
b s-a
19. e at sin ( bt ) 20. e at cos ( bt )
(s - a) (s - a)
2 2
+ b2 + b2
b s-a
21. e at sinh ( bt ) 22. e at cosh ( bt )
(s - a) (s - a)
2 2
-b 2
- b2
n! 1 æsö
23. t ne at , n = 1, 2,3,K 24. f ( ct ) Fç ÷
(s - a)
n +1
c ècø
uc ( t ) = u ( t - c ) e - cs d (t - c )
25. 26. e - cs
Heaviside Function s Dirac Delta Function
27. uc ( t ) f ( t - c ) e F (s)
- cs
28. uc ( t ) g ( t ) e - cs L { g ( t + c )}
ect f ( t ) F ( s - c) t n f ( t ) , n = 1, 2,3,K ( -1) F ( n) ( s )
n
29. 30.
1 ¥ t F (s)
31. f (t ) ò F ( u ) du 32. ò f ( v ) dv
t s 0
s
T
t
ò e - st f ( t ) dt
33. ò f ( t - t ) g (t ) dt F (s)G (s) 34. f (t + T ) = f (t ) 0
0
1 - e - sT
35. f ¢ (t ) sF ( s ) - f ( 0 ) 36. f ¢¢ ( t ) s 2 F ( s ) - sf ( 0 ) - f ¢ ( 0 )
37. f ( n) ( t ) s n F ( s ) - s n-1 f ( 0 ) - s n- 2 f ¢ ( 0 )L - sf ( n- 2) ( 0 ) - f ( n-1) ( 0 )
8 Probability and Moment Generating Functions Conditional mean and variance
σX
E [X | Y ] = E [X] + ρ (Y − E [Y ])
• GX (t) = E tX |t| < 1
"∞ σY
∞
#
X (Xt)i X E Xi
· ti
t
Xt
• MX (t) = GX (e ) = E e =E =
p
i! i! V [X | Y ] = σX 1 − ρ2
i=0 i=0
• P [X = 0] = GX (0)
• P [X = 1] = G0X (0) 9.3 Multivariate Normal
(i)
GX (0) Covariance Matrix Σ (Precision Matrix Σ−1 )
• P [X = i] =
i!
V [X1 ] · · · Cov [X1 , Xk ]
• E [X] = G0X (1− )
Σ=
.. .. ..
(k)
• E X k = MX (0) . . .
X!
Cov [Xk , X1 ] · · · V [Xk ]
(k)
• E = GX (1− )
(X − k)! If X ∼ N (µ, Σ),
2
• V [X] = G00X (1− ) + G0X (1− ) − (G0X (1− ))
−1/2 1
• GX (t) = GY (t) =⇒ X = Y
d
fX (x) = (2π)−n/2 |Σ| exp − (x − µ)T Σ−1 (x − µ)
2
Properties
9 Multivariate Distributions
• Z ∼ N (0, 1) ∧ X = µ + Σ1/2 Z =⇒ X ∼ N (µ, Σ)
9.1 Standard Bivariate Normal • X ∼ N (µ, Σ) =⇒ Σ−1/2 (X − µ) ∼ N (0, 1)
p • X ∼ N (µ, Σ) =⇒ AX ∼ N Aµ, AΣAT
Let X, Y ∼ N (0, 1) ∧ X ⊥
⊥ Z with Y = ρX + 1 − ρ2 Z
• X ∼ N (µ, Σ) ∧ a is vector of length k =⇒ aT X ∼ N aT µ, aT Σa
Joint density 2
x + y 2 − 2ρxy
1
f (x, y) = exp − 10 Convergence
2(1 − ρ2 )
p
2π 1 − ρ2
Conditionals Let {X1 , X2 , . . .} be a sequence of rv’s and let X be another rv. Let Fn denote
the cdf of Xn and let F denote the cdf of X.
(Y | X = x) ∼ N ρx, 1 − ρ2 (X | Y = y) ∼ N ρy, 1 − ρ2
and
Types of Convergence
Independence D
X⊥
⊥ Y ⇐⇒ ρ = 0 1. In distribution (weakly, in law): Xn → X
1
z
(∀ε > 0) lim P [|Xn − X| > ε] = 0
n→∞
f (x, y) = exp −
2(1 − ρ2 )
p
2πσx σy 1−ρ 2
as
3. Almost surely (strongly): Xn → X
" 2 2 #
x − µx y − µy x − µx y − µy h i h i
z= + − 2ρ P lim Xn = X = P ω ∈ Ω : lim Xn (ω) = X(ω) = 1
σx σy σx σy n→∞ n→∞
9
Fourier Transform Table
x(t ) X (f ) X (ω )
δ (t ) 1 1
1 δ (f ) 2πδ (ω )
δ (t − t0 ) e − j 2π ft0 e − jω t0
e j 2π f0t δ (f − f0 ) 2πδ (ω − ω0 )
cos(2π f0t ) 1 π δ (ω − ω0 ) + δ (ω + ω0 )
δ (f − f0 ) + δ (f + f0 )
2
sin(2π f0t ) 1 − jπ δ (ω − ω0 ) − δ (ω + ω0 )
δ (f − f0 ) − δ (f + f0 )
2j
rect (t ) sin c(f ) ω
sin c
2π
sin c(t ) rect (f ) ω
rect
2π
Λ(t ) sin c 2 (f ) ω
sin c 2
2π
sin c 2 (t ) Λ (f ) ω
Λ
2π
e −α t u(t ), α > 0 1 1
α + j 2π f α + jω
te −α t u(t ), α > 0 1 1
2
(α + j 2π f ) (α + jω )2
e −α |t |, α > 0 2α 2α
2 2
(α + (2π f ) (α + (ω )2
2
e −π t e −α f e −α f
2 2 2
sgn(t ) 1 2
jπ f jω
u(t ) 1 1 1
δ (f ) + πδ (ω ) +
2 j 2π f jω
d j 2π f jω
δ (t )
dt
∞ ∞ ∞
1 n 1 2π n
∑ δ (t − nT0 )
T0 ∑ δ f −
T0 T0 ∑ δ ω − T0
n =−∞ n =−∞ n =−∞